2014
DOI: 10.1088/1748-6041/9/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of strontium-doped calcium polyphosphate particles on cytokines from macrophages and osteoblasts leading to aseptic looseningin vitro

Abstract: Aseptic loosening is a common cause of joint implant failure in humans. In order to enhance implant stability, we need to develop a new material that not only promotes the wear resistance of components of an artificial joint, but also possesses the pharmaceutical efficacy of protecting patients against aseptic loosening. Strontium-doped calcium polyphosphate (SCPP) has been found to have this potential ability. The goal of this study is to respectively quantify the levels of TNF-α (for macrophages), receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
4
19
0
1
Order By: Relevance
“…Recently strontium was found to block TNF- α induced NF κ B signal transduction and in another article it was found to inhibit inflammatory mediators production by human monocytes [79]. All of these developments make strontium suitable for use in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently strontium was found to block TNF- α induced NF κ B signal transduction and in another article it was found to inhibit inflammatory mediators production by human monocytes [79]. All of these developments make strontium suitable for use in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse macrophage cell lines (RAW264.7) were the most used [4,6,27,28,29,30,31,32,33,34,35,36,37], followed by OB precursors derived from mouse calvaria (MC3T3-E1) [27,28,38,39,40,41] and human (Saos-2 and MG-63) [1,42,43] or rat (ROS 17/2.8) [44] osteosarcoma and monocitic (THP-1) [20,45,46] cell lines. In addition, other studies also used primary cells: mouse [28,47] or human [42,48] OBs, mouse or rat bone-marrow-derived macrophages (BMM) [28,49,50,51], human MSCs [39,52], mouse [47] or human [53] FBs and mouse peritoneal macrophages [54].…”
Section: Gene Expression In Osteolysismentioning
confidence: 99%
“…Sr cannot show positive clinical and histopathological effects on the tissues with radiodermatitis, which may be due to the severity of radiodermatitis and concentration of the administered treatment. It was found that Sr blocks TNF-α related to nuclear factor-κB signaling pathway and inhibits the release of inflammatory mediators from monocytes 21,25 . In this study, there were significantly higher TNF-α values between the control group and group 2 that had only RT, and group 8 that had cream application before and after RT.…”
Section: Figurementioning
confidence: 99%